Hate Crime Reporting: The Relationship Between Types of Barriers and Perceived Severity - Vergani, Matteo (European journal on criminal policy and research, 2023)
Previous research has identified numerous barriers to reporting hate crimes. However, high variability exists in the outcome measures considered across multiple studies, including whether hate crimes encompass non-criminal behaviours, whether victims’ perceptions are considered bias indicators, and whether the incident is reported to police or to other organisations. These inconsistencies prevent an understanding of whether different barriers relate to different types of hate crimes. This article presents the results of an exploratory empirical study with a convenience sample of members of minorities facing hate crime victimisation in Victoria, Australia (N = 260). Our study participants experienced different types of barriers regarding incidents with different levels of perceived severity. Internalisation and lack of knowledge were more relevant to the underreporting of incidents perceived as less serious—verbal assault. Fear of consequences, lack of trust in statutory agencies, and accessibility were more relevant to the underreporting of incidents perceived as more serious—physical violence and property destruction.